A Randomized Trial of Punctuated Antiretroviral Therapy in Ugandan HIV-Seropositive Adults With Pulmonary Tuberculosis and CD41 T-Cell Counts of $350 cells/lL - Nanteza, M. W.; Mayanja-Kizza, H.; Mupere, E.; Mugyenyi, P.; Mugerwa, R. D.; Havlir, D. V. (Journal of Infectious Diseases, 2011)
Optimal treatment of human immunodeficiency virus (HIV)–associated tuberculosis in patients with high CD4+ T-cell counts is unknown. Suppression of viral replication during therapy for tuberculosis may block effects of immune activation on T cells and slow HIV disease progression. We conducted a randomized trial in 214 HIV-infected patients with active tuberculosis and CD4+ T-cell counts of ≥350 cells/μL to determine whether 6 months of antiretroviral therapy given during tuberculosis treatment would improve clinical outcomes. Subjects were randomized to receive 6 months of abacavir-lamivudine-zidovudine concurrent with tuberculosis therapy or delayed antiretroviral therapy. Endpoints were CD4+ T-cell counts of <250 cells/μL, AIDS, or death. Intervention and comparison arms had similar median CD4+ counts (517 and 534 cells/μL, respectively) and HIV RNA levels (4.6 and 4.7 log10 copies/μL, respectively). Viral suppression was achieved in 86% of patients allocated to intervention. Seventeen subjects (15.6%) in the intervention arm developed study outcome compared to 25 subjects (22.8%) in the comparison arm (P = .17). Grade 3 or 4 adverse events were less frequent in the intervention arm. By 2 months, 90% of subjects in both arms were culture-negative for tuberculosis.Short-term antiretroviral therapy during tuberculosis treatment in patients with CD4+ T-cell counts of >350 cells/μL was safe and associated with clinical benefits.
Keywords: acquired immunodeficiency syndrome; pulmonary tuberculosis; surrogate endpoints